MEASUREMENT OF MAGNETIC SUSCEPTIBILITY OF SUBSTANCES IN THE CONDITIONS OF DISTANCE EDUCATION - Zdeshchyts, Valeriy; Zdeshchyts, Anastasiia (Physical and Mathematical Education, 2023)
A technique and experimental setup was developed for conducting laboratory work in physics, which uses electronic scales to determine the functional dependence of the force of interaction between two permanent magnets, between a magnet and a ferromagnet depending on the distance between them, as well as the magnetic susceptibility of para-, dia- and ferromagnets. Formulation of the problem. Calculating the magnitude of the magnetic induction of a permanent magnet at some distance using the Biot-Savart-Laplace law is a very difficult task for students of introductory courses. As polls have shown, students almost unanimously believe that the force of interaction between two magnets depends inversely quadratic on the distance between them. Therefore, only the experiment allows novice students to answer this question. Attempting to classify materials according to the magnetic-non-magnetic feature is also a problem for students. Experimental measurement of the magnetic susceptibility of substances will allow students to correctly conclude that all materials are magnetized. Materials and methods. The authors developed a measurement scheme and a research setup, which provided for the possibility of its reproduction by students during distance learning. With the help of electronic scales and neodymium magnets, the dia- and paramagnetic properties of various substances found in the students’ everyday environment were determined. Results. The main result of the work is the development of a methodology to demonstrate to students the fact that the laws used to describe the magnetic fields of permanent magnets are not "inverse quadratic". Conclusions. The inverse cubic dependence of magnetic induction on distance was experimentally confirmed; the force of interaction between two permanent magnets is proportional to , between a magnet and a ferromagnet . The magnetic susceptibility of ferromagnet (iron), paramagnet (aluminum) , diamagnet (water) was determined.